Implementasi Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Desa Waduk Kecamatan Takeran Kabupaten Magetan - Yoga Adhiguna; Fifiana Wisnaeni (Notarius, 2022)
AbstractThe purpose of this study to find out how the procedure for land enlistment through the Complete Systematic Land enrollment program (PTSL). Find out what obstacles are faced in the Complete Systematic Land registration program (PTSL)and how to solve it. The results of the research and discussion is: the village that wants to register for PTSL must make a letter of application; determine the location and number of fields; conducting counseling or socialization; establishment and Determination of PTSL Adjudication Committee; collection of Physical Data and Juridical Data Collection; juridical data research to prove land rights; affirmation of conversion, recognition of rights and granting rights to land; accounting for land rights; issuance of certificates of land rights and documentation and submission of results of activities. Constraints experienced in the execution of Complete Systematic Land Registration (PTSL) in Waduk Village are limited human resources in the process of processing and collecting data and the limited time specified.Keywords : implementation; land registration; Complete Systematic Land enrollment.AbstrakPenelitian ini mempunyai tujuan untuk mengetahui prosedur pendaftaran tanah melalui program Pendaftaran Tanah Sistematik Lengkap (PTSL) dan kendala yang dihadapi dalam program Pendaftaran Tanah Sistematik Lengkap (PTSL) dan bagaimana upaya penyelesaiannya. Metode penelitian yang digunakan adalah empiris, lokasi penelitian di Desa Waduk, Kecamatan Takeran , Kabupaten Magetan. Hasil penelitian dan pembahasan adalah: desa yang ingin mendaftar PTSL harus membuat surat permohonan; melakukan penetapan lokasi dan jumlah bidang; melakukan penyuluhan atau sosialisasi; pembentukan dan Penetapan Panitia Ajudikasi PTSL; pengumpulan Data Fisik dan Pengumpulan Data Yuridis; penelitian data yuridis untuk pembuktian hak atas tanah; penegasan konversi, pengakuan hak dan pemberian hak atas tanah; pembukuan hak atas tanah; penerbitan sertipikat hak atas tanah dan pendokumentasian dan penyerahan hasil kegiatan. Kendala yang dialami dalam pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Desa Waduk adalah keterbatasan sumber daya manusia dalam proses pengerjaan dan pengumpulan data serta keterbatasan waktu..Kata kunci : implementasi; pendaftaran tanah; pendaftaran tanah sistematis lengkap